Biopsychosocial rehabilitation therapy in small fiber neuropathy: research protocol to study the effect of rehabilitation treatment - Damci, Aysun; den Hollander, Marlies; Hoeijmakers, Janneke G. J.; Faber, Catharina G.; Goossens, Mariëlle E. J. B.; Verbunt, Jeanine A. M. C. F. (Frontiers in Neurology, 2024)
BackgroundSmall fiber neuropathy (SFN) is a chronic neuropathic pain condition that can lead to a decreased quality of life (QOL) and disability. Current pain treatment is mainly symptomatic, consisting of analgesics, with often disappointing results. There is a need for new, more effective treatment modality. Treatment based on a biopsychosocial approach on SFN-related pain may be a promising alternative. A rehabilitation treatment study protocol is presented with the following main objective: to test the effect of a tailored interdisciplinary rehabilitation treatment targeting both cognitive and psychological factors related to pain, in decreasing disability, and improving QOL in SFN.MethodsSingle-case experimental design. Ten participants with SFN will be included. Every patient will be offered a personalized program based on one of three rehabilitation treatment modules (graded activity, exposure in vivo or acceptance and commitment therapy) depending on the most prominent factor maintaining disability. Treatment will be provided for at least 8 weeks with 2 sessions a week.Discussion/conclusionThis is the first study investigating personalized rehabilitation treatment in patients with idiopathic SFN. The findings are expected to result in an effective treatment for SFN with an increase in QOL and a decrease in disability.Clinical trial registrationClinicalTrials.gov, identifier NCT05798949.